Impact of travel distance on outcomes for clinical trial patients: the Kinghorn Cancer Centre experience. Issue 2 (3rd August 2022) - Lim, Jennifer; Akbar Ali, Syafiq; Prawira, Amy; Sim, Hao‐Wen
Abstract: Background: Geographic isolation and travel distance to specialist care is a known social determinant of health and contributes to poorer oncology survival outcomes. Aims: To compare survival and toxicity outcomes for patients travelling long distances (>50 km) for treatment on clinical trials with local patients (<10 km and 10–50 km). Methods: We performed a retrospective cohort study based at the Kinghorn Cancer Centre, a comprehensive cancer care centre in metropolitan Sydney. We included adult patients with advanced solid‐organ malignancies who were enrolled on therapeutic clinical trials between July 2015 and December 2017. Outcome measures included overall survival, progression‐free survival, rates of grade 3–4 toxicity and unplanned hospital admissions for the duration of the clinical trial. Results: We included 173 patients, of whom 27% lived within 10 km, 29% lived between 10 and 50 km and 44% lived further than 50 km. We did not identify significant differences between survival or toxicity outcomes between patients travelling long distances and local patients. Conclusions: All patients should be considered for clinical trial referral based on clinical parameters and preference, regardless of geographic proximity. In the meantime, improving access to clinical trials for rural and regional patients continues to be a priority.